Evaluasi Dosis Pemupukan Rekomendasi Kementerian Pertanian untuk Tanaman Padi - Arief Hartono; Muhammad Firdaus; Purwono Purwono; Baba Barus; Mimin Aminah; Denis Muba Pandapotan Simanihuruk (Jurnal Ilmu Pertanian Indonesia, 2022)
Rice is a strategic commodity, so efforts to increase its production continue to be carried out, one of which is by increasing fertilization efficiency. The government has set policies in the field of fertilization, one of which is to provide fertilizer recommendations for rice plants based on specific location. The objective of this research was to evaluate the fertilization policy written in Permentan RI No. 40/Permentan/OT.140/4/2007. The methods were analyzing the variance values for each type of fertilizer recommended and validating N, P, and K levels in selected locations. The results of the study showed that the fertilization recommendations set by the government still need to be improved because there were still many discrepancies with conditions in the field. The adjustment of recommendation dose with the addition of organic materials were relevant and can be implemented, but it is still required further socialization to farmers. Reformulation of subsidized fertilizers, from NPK fertilizer 15-15-15 to NPK fertilizer 15-10-12 also had not been able to increase fertilization efficiency, because it actually made the dose of NPK becomes higher, but did not reduce the addition of a single fertilizer significantly. Subsidy policy also needs to be reviewed, because farmers did not fully get subsidized fertilizer so the farmers could not meet the needs of their fertilizers. Regarding the implementation of fertilization information, a soil big database must be created nationally to make specific location fertilization recommendations, and this must be easily accessed by farmers. Keywords: fertilization policy, organic material, soil big database, subsidy